Political Competition with Endogenous Party Formation and Citizen Activists - Emanuel Hansen (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper studies the effects of endogenous party formation on political platforms. It develops a model in which parties allow like-minded citizens to, first, share the cost of running in a public election and, second, coordinate on a policy platform. The paper characterizes the set of political equilibria with two competing parties and with one uncontested party. In two-party equilibria, the distance between both platforms is always positive but limited, in contrast to the median voter model and the citizen candidate model. In one-party equilibria, the median voter can be worse off than in all equilibria with two competing parties.
Keywords: D71; D72; 330; elections; party formation; platform choice; electoral uncertainty